2021
DOI: 10.1177/22125868211045778
|View full text |Cite
|
Sign up to set email alerts
|

The China-centric era? Rethinking academic identity for sustainable higher education internationalization in China

Abstract: Although recent decades have witnessed remarkable development of China’s higher education (HE) since its Open Door policy in 1978, China’s cross-border collaboration in HE has not always been smooth. The global rise of neo-nationalism in recent years, exacerbated by the COVID-19 crisis, has put international academic collaboration under grave threat. This conceptual article first conducts a critical review of China’s strategy for HE internationalization to discern its underlying rationale and what is encumberi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This experience indicates that international returnees, who had global views and knowledge, needed to adapt to national and local cultural contexts, including in relation to academic writing standards, and management systems. This change perhaps reflects more of the balanced academic identity development encouraged more recently (Li, 2021b).…”
Section: During the Transition Phase: Global As Inflected Through Nat...mentioning
confidence: 99%
See 1 more Smart Citation
“…This experience indicates that international returnees, who had global views and knowledge, needed to adapt to national and local cultural contexts, including in relation to academic writing standards, and management systems. This change perhaps reflects more of the balanced academic identity development encouraged more recently (Li, 2021b).…”
Section: During the Transition Phase: Global As Inflected Through Nat...mentioning
confidence: 99%
“…Notably, Xu et al (2019) found that although Chinese academic research has become increasingly visible, and the international influence of Chinese academic studies has expanded, many locally trained scholars still face difficulties because of limited English writing skills and maintaining Chinese characteristics alongside international recognition. In the context of rising nationalism, Li (2021b) has argued that Chinese scholars should construct a more balanced academic identity between more national and international dimensions.…”
Section: Academic Identity Formationmentioning
confidence: 99%